Partial Closure of Skin Wounds after Kidney Transplantation Decreases the Incidence of Postoperative Wound Infections - Siskind, Eric; Huntoon, Kristin; Shah, Kavin; Villa, Manuel; Blood, A.J.; Lumerman, Leandro; Fishbane, Lara; Goncharuk, Edwin; Oropallo, Alisha; Bhaskaran, Madhu; Sachdeva, Mala; Jhaveri, Kenar D.; Calderon, Kellie; Nicastro, Jeffrey; Coppa, Gene; Molmenti, Ernesto P. (International Journal of Angiology, 2012)
Wound infections are a major cause of morbidity after kidney transplantation. The purpose of our study was to evaluate an improved technique of wound closure. Data corresponding to 104 consecutive live donor kidney recipients were prospectively collected and analyzed. Our routine standard technique involved closure of the abdominal wall muscle and fascia in one layer with interrupted nonabsorbable full thickness sutures. No drains were used. The skin was closed with interrupted 2–0 nylon sutures 4 to 5 cm apart, leaving the skin and subcutaneous tissue in between partially open. Patients were allowed to shower starting on the first postoperative day. Examination of the wounds was continued for at least 1 month postoperatively, and then routinely as needed. All patients were thoroughly informed preoperatively of our technique. There were no immediate postoperative wound infections. There were no instances of dehiscence, evisceration, or need for revision. All patients were able to continue with their routine daily activities. Cosmetic results were satisfactory in all cases. We did not experience any patient complaints with respect to our technique. Patient satisfaction scores conducted by Press Ganey and Associates ranked in the 99 percentile with respect to peers undergoing kidney transplantation. Three patients returned six months postoperatively with suture granulomas which were treated nonoperatively. Partial closure of the skin wound with no associated drains is an effective and cosmetically desirable way to decrease the incidence of postoperative infections in kidney transplantation.
Keywords: kidney transplantation; wound infection; wound closure; immunosuppression; transplant surgery